Evaluasi Program Mentoring Agama Islam dalam Meningkatkan Komitmen Beragama - Gilang Faisal Andrian; N. Kardinah; Ening Ningsih (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2018)
Islamic mentoring in a senior high school in Bandung has not been thoroughly evaluated. Thus, the researchers conducted an evaluation of the mentoring program to see its effectiveness in enhancing religious commitment as the goal of carrying out these activities. This is an evaluative research with quantitative and qualitative approaches. The study sample consisted of 38 IRMa Luqman members. This study used a program evaluation scale and religious commitment scale, as well as interviews as supporting data. Descriptive percentage analysis and interviews are used to find out the results qualitatively, while the comparative analysis uses the paired sample t-test to find out the results quantitatively. Evaluation results show that mentoring activities have run quite effectively, also religious commitment of respondents increased significantly. Thus, it can be concluded that the islamic mentoring program is effective enough to increase religious commitment to IRMa Luqman members at SMAN 10 Bandung.